Stable isotopes reveal spatial variability in the trophic structure of a macro‐benthic invertebrate community in a tropical coral reef1. (11th January 2016) - Kolasinski, Joanna; Nahon, Sarah; Rogers, Karyne; Chauvin, Anne; Bigot, Lionel; Frouin, Patrick
Abstract : Rationale: Studies of organic matter fluxes in coral reefs are historically based on physical and biogeochemical approaches. It is important to link these approaches to community analysis as the abundance and behaviour of species, populations or trophic groups can have a profound effect on nutrient budgets. Methods: We determined the carbon and nitrogen isotopic compositions of coral reef organic matter sources and macro‐benthic invertebrate communities using a Europa Geo 20/20 isotope ratio mass spectrometer interfaced to an ANCA‐SL elemental analyzer in continuous flow mode. Isotopic ecology metrics and a mixing model were used to analyze and interpret the data. Results: The coral reef macro‐invertebrate community principally relies on detrital or recycled food sources. An increased reliance on reef nitrogen‐derived sources was observed in the cold‐dry season. The community food‐web lengths differ noticeably across the coral reef and reflect the characteristics and origin of organic matter reservoirs. Conclusions: Anthropogenic and terrestrial inputs lead to a loss of biological diversity. Exclusive dominance of suspension‐feeding species is observed in areas receiving direct surface riverine particulate organic matter. The accumulation of sediment organic matter in eutrophic areas leads to dominance of deposit‐feeding species. Copyright © 2016 John Wiley & Sons, Ltd.